Evaluation of different oil sources for nursery pigs - Jordan, Kyle E.; Goncalves, Marcio Antonio Dornelles; DeJong, John A.; Woodworth, Jason C.; Tokach, Michael D.; Dritz, Steven S.; Goodband, Robert D.; DeRouchey, Joel M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
A total of 210 pigs (PIC 327 × 1050, initially 28.9 lb BW) were used in a 21-d trial to evaluate the effects of increasing oil sources on nursery pig growth performance. The 2 oil sources included a commercial source of soybean oil and a proprietary source of corn oil originating from the ethanol industry (Corn Oil ONE, Feed Energy Co., Pleasant Hill, IA). The 5 experimental diets included: a control diet without added oil, diets with 2.5 or 5% added soybean oil, or diets with 2.5 and 5% added corn oil. Diets were formulated with an identical standardized ileal digestible lysine:calorie ratio and were fed in meal form. There were 6 pens per treatment with 7 pigs per pen. Overall, from d 0 to 21, no oil source × level interactions were observed. Increasing corn oil or soybean oil had no effect on ADG or final BW. Increasing corn oil or soybean oil decreased (linear, P < 0.05) ADFI, which resulted in improved (linear, P < 0.01) F/G. Caloric efficiency was not affected by oil source or level. Feed cost per pig tended to decrease (linear, P = 0.066) for pigs fed increasing levels of soy oil. Cost per pound of gain decreased for both Corn Oil ONE (linear, P = 0.032) and soybean oil (linear, P = 0.008) as oil level increased. Value of the weight gain and income over feed cost was similar for pigs fed diets with Corn Oil ONE and soybean oil (P = 0.833). This study shows the benefits of adding a dietary oil source in late-phase nursery diets to achieve improved feed efficiency. Corn Oil ONE is a suitable alternative for soybean oil, and cost and availability should dictate which source is used.
Swine Industry Day, 2014 is known as Swine Day, 2014
Keywords: Corn oil; Growth performance; Nursery pig; Soybean oil